The experience in Dewey and Larrosa (Revista Apotheke, 2026)
This article analyzes the contributions of John Dewey and Jorge Larrosa Bondía on experience in education, highlighting their distinct approaches and their implications for contemporary pedagogical practice. Dewey conceives of experience as a dynamic process where the subject is active in the construction of knowledge, emphasizing practical and reflective interaction as the basis for learning. On the other hand, Larrosa criticizes the superficiality of current knowledge, arguing that true experience should be a profound and transformative experience, in contrast to the incessant search for information. The main objective of the research is to carry out a comparative analysis of the conceptions of experience of both authors, exploring how these views can enrich educational practice. The methodology adopted is qualitative, with a bibliographic review of the fundamental works of Dewey and Larrosa, such as Democracy and Education and Tremors: Writings on Experience. The results indicate that, while Dewey values practical action, Larrosa emphasizes the subjectivity and depth of lived experience. Integrating these perspectives can lead to more meaningful learning, with Dewey’s reflective practice complemented by Larrosa’s attention to subjectivity. It is concluded that an education that values experience in its practical and subjective dimensions can develop individuals who are more critical and aware of their social role, promoting transformative learning.
Keywords: Experience; Education; John Dewey; Jorge Larrosa; Pedagogical practice